Global Communication - Slutskiy, Pavel. author. aut Link
XI, 176 p. 8 illus., 6 illus. in color.
Keywords: This textbook equips students with essential media and communication skills for today’s interconnected world. Developed as a key companion text for the Global Communication Project (GlobCom), an initiative spanning five continents, the book presents the key concepts that underpin effective communication on a global scale and guides the reader through project development, covering cross-cultural communication processes and virtual collaboration dynamics. In today’s rapidly evolving global communication landscape, professionals with expertise in global public relations (PR) are in high demand. For students looking to develop their global PR competences, the GlobCom Project offers an authentic experience aligned with industry expectations and is a platform for related courses to draw from. This textbook provides both theoretical and practical material to enhance students’ learning experience, and serves as a valuable resource for lecturers and advanced undergraduate and graduate students in the media, marketing communication, and PR fields. By offering insights into the complexities of international communication, it helps aspiring and current professionals become skilled and globally aware in their approach to global communication. .